BAFF Mediates Splenic B Cell Response and Antibody Production in Experimental Chagas Disease - Bermejo, Daniela A. (Public Library of Science, 2010)
BACKGROUND: B cells and antibodies are involved not only in controlling the spread of blood circulating Trypanosoma cruzi, but also in the autoreactive manifestations observed in Chagas disease. Acute infection results in polyclonal B cell activation associated with hypergammaglobulinemia, delayed specific humoral immunity and high levels of non-parasite specific antibodies. Since TNF superfamily B lymphocyte Stimulator (BAFF) mediates polyclonal B cell response in vitro triggered by T. cruzi antigens, and BAFF-Tg mice show similar signs to T. cruzi infected mice, we hypothesized that BAFF can mediate polyclonal B cell response in experimental Chagas disease. METHODOLOGY/PRINCIPAL FINDINGS: BAFF is produced early and persists throughout the infection. To analyze BAFF role in experimental Chagas disease, Balb/c infected mice were injected with BR3:Fc, a soluble receptor of BAFF, to block BAFF activity. By BAFF blockade we observed that this cytokine mediates the mature B cell response and the production of non-parasite specific IgM and IgG. BAFF also influences the development of antinuclear IgG and parasite-specific IgM response, not affecting T. cruzi-specific IgG and parasitemia. Interestingly, BAFF inhibition favors the parasitism in heart. CONCLUSIONS/SIGNIFICANCE: Our results demonstrate, for the first time, an active role for BAFF in shaping the mature B cell repertoire in a parasite infection.